2019
DOI: 10.1021/acsomega.8b02207
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteomic Profiling Provides Candidate Myocardial Infarction Predictors of Later Progression to Heart Failure

Abstract: We hypothesized that identifying plasma glycoproteins that predict the development of heart failure following myocardial infarction (MI) could help to stratify subjects at risk. Plasma collected at visit 2 (2005–2008) from an MI subset of Jackson Heart Study participants underwent glycoproteomics and was grouped by the outcome: (1) heart failure hospitalization after visit 2 (n = 15) and (2) without hospitalization by 2012 (n = 45). Proteins were mapped for biological processes and functional pathways using In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…[9] More recently, Deleon-Pennell et al found, using a glycoproteomic profiling, that Apo-F is independently associated with the risk of later progression to HF after myocardial infarction in humans. [26] Finally, we previously published that Apo-J is involved in cardiac cell hypertrophy and is a potential biomarker of left ventricular remodeling following myocardial infarction. [27] More recently, we showed that this increased levels of Apo-J is due to a defect in protein degradation systems activity.…”
Section: Discussionmentioning
confidence: 99%
“…[9] More recently, Deleon-Pennell et al found, using a glycoproteomic profiling, that Apo-F is independently associated with the risk of later progression to HF after myocardial infarction in humans. [26] Finally, we previously published that Apo-J is involved in cardiac cell hypertrophy and is a potential biomarker of left ventricular remodeling following myocardial infarction. [27] More recently, we showed that this increased levels of Apo-J is due to a defect in protein degradation systems activity.…”
Section: Discussionmentioning
confidence: 99%
“…Of the seven proteins passing correction for multiple testing, three have previously been put forward as cardiovascular makers: apolipoprotein C-IV (APOC4) is a lipid-binding protein belonging to the apolipoprotein gene family, and the gene is located in the so-called APOE - APOC1 - APOC4 - APOC2 gene cluster, which has been intensively studied in relation to cardiovascular traits and risk factors, e.g., [ 23 ]. With respect to proteome studies, APOC4 has been reported to be associated with coronary atherosclerosis [ 24 ], heart failure after AMI [ 25 ], and recovery from stroke [ 26 ]. Additionally, lipopolysaccharide-binding protein (LBP) has been reported as a protein marker of AMI [ 13 ] and to be associated with coronary atherosclerotic plaque disruption [ 27 ], as well as a risk of AMI after human immunodeficiency virus [ 28 ] or COVID-19 infection [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glycoproteomic analysis of human atrial extracellular matrix proteins, using lectin‐based glycoprotein enrichment, identified 65 N ‐ and O ‐linked glycosylation sites in 35 proteins, with several showing differential expression between the left and right atria [116]. PTMs also show putative potential as biomarkers of heart failure, with 14 of 198 glycopeptides identified in human plasma showing differential expression in post‐MI patients who required subsequent rehospitalization versus those who did not [117], suggesting candidate glycoproteins as predictors of future heart failure progression.…”
Section: Modification‐specific Proteomics In the Heartmentioning
confidence: 99%